Penerapan Metode Bermain Peran untuk Meningkatkan Kemampuan Bersosialisasi Pada Pendidikan Anak Usia Dini - Aida, Nurul; Rini, Rr. Amanda Pasca (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
This study aims to contain a statement that proves the influence the play of role methods to social skills of children. The subjects were 15 children and the characteristics of the subjects are: a ) children aged 4-5 years ( group A ) , b ) indicates a low social skills. The study design used one group pre - test - post - test design. Measuring instruments in this study used the Social Ability Scale from Likert Scale adaptation ( Scale Social Ability ) . Method of analysis used Mann - Whitney / Wilcoxon , to know descriptives Statistics for different test scores of pre - test and post - test . The Results of Mann - Whitney / Wilcoxon inter- rater high enough ( pre - test and post-test 86.80 154.07 . Results of Mann - Whitney / Wilcoxon shows that learning to play of role method can improve social skills of early childhood ( p = 0.000 ).